Preemptive effects of epidural s (+) - ketamine or ketamine in the horse's postincisional pain - Oleskovicz, Nilson; Valadão, Carlos Augusto Araújo; M, Juan Carlos Duque; Farias, Anderson (Brazilian Journal of Veterinary Research and Animal Science, 2006)
The aim of this study was to evaluate the pre-emptive effect of epidural ketamine S (+) (SK) or racemic ketamine (RK) administration, in post-incisional pain in horses. Were used in a blinded, randomized experimental study, sixteen mixed breed mares, 6±2 years old, weighting 273.2±42.0 kg. An epidural catheter was inserted 24 hours before the trials. The thigh region was shaved bilaterally, and mechanical cutaneous sensibility was measured using von Frey filaments (T-30). Using the left side as the control one, local anesthesia was performed at the right side. Twenty-five minutes later, SK was injected in G1 or RK in G2 through the epidural catheter. Five minutes after the ketamine injection, a 10 cm skin incision was made on the right side, and then sutured. Mechanical post-incisional pain was measured using von Frey filaments, at 1, 3 and 5 cm around the incision at 15 minutes intervals, for 2 hours, then 4, 6 and 8 hours after suturing. No changes were observed in the heart and respiratory rate and rectal temperature among groups or times of each group. Hind limb ataxia was observed in 62.5% and 12.5% of G1 and G2 respectively. SK and RK reduced cutaneous sensibility in the right and the left sides to mechanical postincisional pain during all time of experiment. Epidural SK and RK produce similar post-incisional analgesic effects, did not interfere in the cardio-respiratory parameters. The SK induces more intense ataxia in mares and presents a larger analgesic potency in the first 60 minutes after the administration.